2021
DOI: 10.2478/nor-2021-0012
|View full text |Cite
|
Sign up to set email alerts
|

Renegotiating quality TV in the Swedish pressAmerican serial television and Sweden's post-monopoly television landscape

Abstract: In this article, I explore the reception of American “quality” serial television in Sweden from 1999 to the mid-2010s. My analysis includes how cultural critics and journalists writing for Sweden's leading newspapers conceptualised American serial television as “quality TV” and as legitimate “art”, and it charts the ways in which these discourses relate to the reconfiguration of Swedish television from public service monopoly to niche-oriented multichannel system. The analysis uncovers a process of cultural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…During much of the first decade of this millennium, the discourse on American 'quality' serial TV in Sweden's leading newspapers was dominated by a widely shared ambition to conceptualize this form of television as a legitimate art object (Frykholm 2021). 4 The key strategies that critics and journalists used for this purpose were these: (a) promotion of television series creators, writers, and showrunners as 'artists'; (b) emphasis (directly or by implication) on the affinities between prestige television and already consecrated forms of art, most notably art cinema and literature; and (c) emphasis on prestige serial TV as a conveyer of realism, complexity, and depth.…”
Section: American Quality Serial Television In Sweden: a Discursive Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…During much of the first decade of this millennium, the discourse on American 'quality' serial TV in Sweden's leading newspapers was dominated by a widely shared ambition to conceptualize this form of television as a legitimate art object (Frykholm 2021). 4 The key strategies that critics and journalists used for this purpose were these: (a) promotion of television series creators, writers, and showrunners as 'artists'; (b) emphasis (directly or by implication) on the affinities between prestige television and already consecrated forms of art, most notably art cinema and literature; and (c) emphasis on prestige serial TV as a conveyer of realism, complexity, and depth.…”
Section: American Quality Serial Television In Sweden: a Discursive Shiftmentioning
confidence: 99%
“…The essay represents the second step in a research project that explores the role of American 'quality' serial television in Swedish cultural life, primarily via a critical analysis of discourses in Sweden's leading newspapers from 1999 to 2018. 3 Step one involved an investigation of how critics and journalists worked in tandem with the culture industries to frame American serial television as legitimate art in a Swedish cultural context (Frykholm 2021). That study also suggested that the agenda of cultural consecration was mostly exhausted after 2012, and replaced by other ways of conceptualizing serial television and its role in Swedish television culture and industry.…”
mentioning
confidence: 99%